Explanation of the Rapid Enlargement of Distances in the Early Universe - Carmesin, Hans-Otto Gerhard (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2020)
The expansion of space since the Big Bang, and the evolution of the early universe in particular, are challenging topics for students in research clubs or similar learning groups. Here we study the conservation of energy during that expansion, the origin of the rapid enlargement in the so-called era of ‘cosmic inflation’ and the origin of the energy and matter in the universe. The results are worked out in full detail here, so that they can be directly used in a learning group.